Description of a new Pergalumna (Acari: Oribatida: Galumnidae) species from Mexico and its postembryonic development - Páez, Jair; Villagomez, Fernando; Palacios-Vargas, Jóse G. (Zootaxa, 2019)
A new species of Pergalumna from soil and litter was reared in laboratory and a description of adult and juveniles is provided. Adults are characterized by having bands of striae in the posterior part of notogaster, the interlamellar seta are longer than all other prodorsal setae and the lenticular area covers most of the prodorsum. It differs from Pergalumna boliviana by having long interlamellar seta, bigger ellipsoidal porose area Aa and the presence of A2; it differs from Pergalumna paraboliviana by the shape of porose areas; i.e. Aa being ellipsoidal and big, A1 is the smallest, Ap is absent and there are longitudinal striate bands on the prodorsum and ventral plate.